Evaluasi Penggunaan Sistem Informasi Akademik Berbasis Web [eCampuz]: Pendekatan Mixed Methods terhadap Kepuasan Pengguna - Immanuel Candra Irawan; Meidyna Renaningdyah Pelenkahu (STMIK Pesat Nabire, 2025)
STMIK Pesat Nabire is a private university in Papua Tengah that uses a web-based academic information system called eCampuz. User satisfaction evaluation plays a crucial role in improving the quality of academic services at an institution. The purpose of this study is to determine the extent of user satisfaction with eCampuz at STMIK Pesat Nabire, identify the factors influencing such satisfaction, and pinpoint the aspects of eCampuz that need to be improved and developed to enhance user satisfaction. This study employs a mixed-methods approach with an explanatory sequential design. The results indicate that the majority of users are satisfied with five key aspects of eCampuz, 80% for System Quality, 80% for Features and Functions, 87% for Security and Privacy, 80% for Usability, and 80% for User Satisfaction. Several shortcomings and challenges were also identified, such as the absence of automatic notifications when instructors post materials, assignments, and attendance records, the lack of date markers on materials posted by instructors, making it difficult for students to distinguish between new and old materials, errors and slow loading times in attendance records, limited file upload capacity, and the inability to accept certain file formats. Regular evaluations of user satisfaction are needed to further improve the system and ensure that user satisfaction is met.